PEMANFAATAN MEDIA PROYEKTOR UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS VIII MATA PELAJARAN BK-TIK TAHUN PELAJARAN 2019 – 2020 - Mat Ali (FKIP, Universitas Billfath Lamongan, 2020)
This study aims to improve learning achievement and mastery of BK-ICT subject material for eighth grade students of SMP Negeri 1 Sekaran. This research is included in class action research. Where the improvement activities carried out as many as three cycles. Data obtained from this study in the form of increased achievement and mastery of students BK_TIK material by using projector media and student learning outcomes using projector media. Research data were obtained using observation sheets and formative tests. From the research that has been done, it is obtained data that the use of projector media can have a positive influence on student learning outcomes. This can be seen from the increasing understanding and mastery of students on the material that has been delivered by the teacher so far (mastery learning increases from cycles I, II, and III), each of which are 55%, 70%, and 90%. In cycle III students' classical learning completeness has been achieved. In addition, the learning model using projector media can be used as an alternative learning media.